Investigating Malay language writing proficiency level among upper secondary school students - Nadzrah Abu Bakar,; Norsimah Mat Awal,; Nor Hashimah Jalaluddin, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This paper aims to present the findings of a research on writing proficiency in Malay language of upper secondary schools students in Malaysia. The research is designed to compare writing patterns of urban and rural students from four different zones. The focus of analysis is divided into three aspects, namely, language used, discourse and idea conceptualization. In language used, the focus is on sentence structure, dialect usage and punctuation while discourse looks at interesting phrases. The ideas in the writings are evaluated holistically by looking at the clarity, maturity and relevance of ideas presented. The respondents of this research are selected from five different zones; Kedah (northern zone), Kelantan (eastern zone), Negeri Sembilan (central zone), Sabah and Sarawak (East Malaysia). The total number of respondents is 1524 students. Generally, the findings of the research show that the writing proficiency of the students is at satisfactory level. However, there are differences in the students’ writing performance within the zones.